2019
DOI: 10.1037/tps0000191
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk/treatment needs and progress protocol for juveniles with sex offenses.

Abstract: With the post-Gault trend toward the criminalization of the juvenile court, the demand for risk prediction assessment scales took on newfound importance. The past several decades of research have underscored the limitations of these scales. To address these limitations, and to shift the focus from current and future risk to least restrictive management strategies and effective treatment, we have developed and implemented a new assessment protocol that relies on risk relevant dynamic factors to inform and indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…-3 of 10 the expert opinion of the authors or a group of stakeholders) (Kang et al, 2019;Pettit et al, 2018;van Minde et al, 2019). Forty six studies (46%) used prospective data collection, and 49 (49%) utilized retrospective data.…”
Section: Resultsmentioning
confidence: 99%
“…-3 of 10 the expert opinion of the authors or a group of stakeholders) (Kang et al, 2019;Pettit et al, 2018;van Minde et al, 2019). Forty six studies (46%) used prospective data collection, and 49 (49%) utilized retrospective data.…”
Section: Resultsmentioning
confidence: 99%
“…The Youth Needs and Progress Development and Implementation Project was initiated in 2016 in order to address the limitations of existing risk tools to assess youths (e.g., developmental immaturity, absence of protective factors, low base rates), and one of its goals was to develop an evidence-informed treatment needs and progress scale (Kang et al, 2019;Prentky et al, 2020). The project led to the development of the Youth Needs and Progress Scale (YNPS; predecessor called Treatment Needs and Progress Scale, TNPS), which comprises 22 dynamic risk and protective factors, along with a few historical items, and is intended to identify risk-relevant intervention needs and track progress among youths and young adults ages 12 to 25 who have engaged in abusive sexual behavior (Righthand et al, 2020; for items see Table 3).…”
Section: Youth Needs and Progress Scalementioning
confidence: 99%
“…[e.g., adjudicated and/or non-adjudicated, males and/or females, youth with low intellectual functioning]); (c) description of the validation sample (i.e., age, gender, adjudication status, and type of setting for research sites [e.g., outpatient vs. residential and/or correctional]; and (d) current literature review of samples studied. Nevertheless, Kang et al (2019) followed to some degree the New Paradigm of risk assessment by incorporating in the TNPS many major aspects of the template of MEGA ♪ , including assessing protective factors and using age groups (in their case -10-14, 15-17, 18-25see p. 159). Prentky et al (2020) completed their pilot study, along with renaming of the tool without explanation to Youth Needs and Progress Scale [YNPS]), and neglect to address many of the multiple concerns raised in Miccio-Fonseca's (2020) critique.…”
Section: Risk Assessment Tools: Risk Prediction and Calibrated Risk Lmentioning
confidence: 99%
“…The multiple cross-validation studies of MEGA ♪ identified a constellation of protective factors interacting to mitigate risk for sexually abusive behaviors, evidencing that protective factors are specific to age and gender (Miccio-Fonseca 2018a). Incorporating protective factors in a risk assessment measure for youth was a substantial turning point in the evolution of risk assessment tools for sexually abusive youth, seen most recently in Kang et al's (2019) new tool, the TNPS.…”
Section: Risk and Protective Factors: Assessing Different Types Of Sementioning
confidence: 99%